F140. Effects of tDCS and HD-tDCS on motor learning and motor maps in children. (May 2018) - Giuffre, Adrianna; Cole, Lauran; Ciechanski, Patrick; Carlson, Helen; Zewdie, Ephrem; Kuo, Hsing-Ching; Kahl, Cynthia; Webber, Amy; Metzler, Megan; Harris, Ashley; Kirton, Adam
Abstract : Introduction: Perinatal stroke is the leading cause of hemiparetic cerebral palsy (CP). We have shown non-invasive brain stimulation enhances motor learning in healthy and hemiparetic children using transcranial-direct-current-stimulation (tDCS). High-definition (HD-tDCS) may offer additional potential but is unstudied in pediatrics. Motor maps are individualized representations of primary motor cortex (M1) topography measurable with single pulse TMS. Advances in MRI-guided imaging and robotic TMS may facilitate rapid and accurate motor mapping. How motor maps are altered by motor learning and tDCS are unknown. We aimed to determine the effects of tDCS/HD-tDCS enhanced motor learning on motor maps in children, hypothesizing tDCS-enhanced learning is associated with motor map enlargement. Methods: AMPED (Accelerated Motor learning in PEDiatrics) is a randomized, sham-controlled trial (NCT03193580). Participants are healthy, right handed children aged 12–18 years. TMS motor mapping is performed using neuronavigated (Brainisght2), robotic (Axilum) TMS. A 10 × 10, 7 mm grid is placed over M1 with 4 stimulations per point generating motor evoked potentials (MEP) of individual hand muscles. Primary outcome is motor map area (volume, center of gravity, cortical excitability are secondary). Motor function is assessed with Purdue Pegboard (primary), Jebsen-Taylor Test, and Serial Reaction Time Task. Participants are randomized into three groups: right M1 1 mA tDCS, HD-tDCS, or sham. All practiced the PPT daily (8 trails) during stimulation with the left hand for 5 consecutive days. Safety and tolerability is assessed daily. All outcomes are repeated on day 5 and at 6 weeks. Two-way repeated measure ANOVA examined changes in performance and motor maps across groups and sessions. Results: Fifteen of 24 participants have completed the study (median age 16.4, 67% female). Blinded interim analysis grouped interventions as A, B, or C. PPT scores improved across all groups (p < 0.001) mean improvement was 3.93(SD:1.3) and comparable across groups: A 4.3(SD 1.7), B 3.1(SD 1.2), C 3.7(SD 1.2). Motor maps were obtained without complication except two subjects could not complete bi-hemispheric mapping due to time constraints. Motor map outcomes differed at baseline between hemispheres −109.31 mm 2 (SD 675.46). Following intervention, map area decreased in group C(−147 ± 65.7), p < 0.04) but change in area was not different between groups. Similar findings were observed for secondary outcomes. Procedures were well tolerated with no adverse events. Conclusion: Trials combining tDCS or HD-tDCS enhanced motor learning with robotic TMS motor mapping are feasible in children. Completion of the sample will determine how HD-tDCS enhancement of motor learning compares to tDCS, with potential to advance therapeutic applications in children with CP.